A low-odor, aging-resistant flame-retardant recycled polypropylene material and preparation method thereof

By modifying the composite adsorbent of Al-MOFs material and fly ash grafted carbon nanotubes, the odor and aging performance problems of regenerated polypropylene materials are solved, and the flame retardant effect with low odor and aging resistance is achieved, which improves the material's Overall performance.

CN115710398BActive Publication Date: 2025-01-07WANHUA CHEMICAL (NINGBO) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211322630.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-01-07
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

In actual application, existing recycled polypropylene materials have problems such as excessive odor and poor thermal oxygen aging performance. Fly ash is an important means of resource utilization, and its effect is poor when directly used as an adsorbent, and there is resource waste and environmental pressure. .

Method used

Modified Al-MOFs materials and fly ash grafted carbon nanotubes are used as composite adsorbents, and the main antioxidant and fly ash are modified through chemical methods for graft modification, combining the adsorption capacity of porous structures to reduce the material odor and Improve aging resistance.

Benefits of technology

It significantly improves the material's thermal oxygen aging ability, reduces odor, and realizes a flame-retardant regenerated polypropylene material with low odor and aging resistance. The odor level is less than 3.5 and the performance retention rate is greater than 75% after 1000 hours of thermal oxygen aging at 150℃. Improves flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003911020610000021
    Figure BDA0003911020610000021
  • Figure BDA0003911020610000061
    Figure BDA0003911020610000061
  • Figure BDA0003911020610000091
    Figure BDA0003911020610000091
Patent Text Reader

Abstract

The present invention provides a low-odor and aging-resistant flame-retardant recycled polypropylene material and a preparation method thereof, wherein the flame-retardant recycled polypropylene material comprises the following components: recycled polypropylene resin, composite adsorbent, modified Al-MOFs, auxiliary antioxidant, lubricant and optional filling material. The present invention utilizes Al-MOFs material to modify the main antioxidant, so that the antioxidant is stably and evenly dispersed in the recycled material, and is not easy to migrate to the surface of the material and cause loss, so that the recycled material has the ability of aging resistance and low odor at the same time; by adding fly ash to graft and modify carbon nanotubes, the specific surface area and adsorption points of fly ash are increased, the dispersion of carbon nanotubes is effectively improved, and while taking into account the odor and aging resistance, the horizontal combustion rate of the composite material is effectively reduced, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of recycled plastics, and in particular relates to a low-odor, aging-resistant, flame-retardant recycled polypropylene material and a preparation method thereof. Background Art

[0002] In recent years, as people's awareness and requirements for green environmental protection have increased, the application of recycled plastics has gradually been promoted. Recycled plastics refer to plastic raw materials that are obtained by processing waste plastics through physical or chemical methods such as pretreatment, melt granulation, and modification. It is the reuse of plastics. Plastics will not rot even if buried underground for hundreds of years, so the awakening of recycling recycled materials is inevitable. In this way, people can truly achieve environmental protection and energy saving through the recycling of resources.

[0003] The biggest advantage of recycled materials is that they are definitely cheaper than new materials. According to different needs, you only need to process certain properties to produce the corresponding products. At present, recycled polypropylene is one of the most recycled and widely used recycled plastics. Although the mechanical properties of recycled polypropylene can basically meet the use requirements in practical applications, they usually have defects such as excessive odor and poor thermal oxidation aging performance.

[0004] Fly ash is a solid waste generated by the operation of coal-fired power plants. Its main components are SiO2 and Al2O3, with a porosity of about 70%. It is a typical porous structure material with a large specific surface area and a certain adsorption capacity. Using the adsorption properties of fly ash to treat heavy metals and organic pollutants in wastewater and waste gas is one of the important means of resource utilization of fly ash. However, due to the complex composition of fly ash and the small number of active adsorption points, the effect of directly using it as an adsorbent to treat waste gas is poor. More importantly, fly ash is a solid waste generated by coal-fired industries such as coal-fired power plants. If it is not used reasonably, it will cause huge waste of resources and environmental pressure.

[0005] CN108530786A discloses a method of obtaining an anti-aging HIPS foam plastic by compounding inorganic anti-aging agents, organic anti-aging agents, antioxidants and other additives, and optimizing the components and dosages. CN109503919A discloses a multifunctional masterbatch for recycled plastics, which uses a variety of additives such as deodorants, defoamers, sealants, etc. to physically blend the masterbatch to have multiple functions for the modification of recycled materials. However, the methods disclosed so far mostly use physically blended additives to compensate for odor or aging performance, and fail to solve the problems of odor and aging at the same time. In addition, there is also the problem of migration loss of antioxidants. Summary of the invention

[0006] The object of the present invention is to provide a low-odor and aging-resistant flame-retardant recycled polypropylene material, which can significantly improve the material's ability to resist thermal oxygen aging while reducing the material's odor.

[0007] Another object of the present invention is to provide a method for preparing the low-odor, aging-resistant, flame-retardant recycled polypropylene material.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0009] A low-odor, aging-resistant, flame-retardant recycled polypropylene material comprising the following components:

[0010]

[0011] In a specific embodiment, the regenerated polypropylene resin is recycled polypropylene regenerated material, preferably with a filler content of less than 5%;

[0012] Preferably, the recycled polypropylene resin has a melt index of 10-50 g / 10 min at 230° C. and 2.16 kg.

[0013] In a specific embodiment, the modified Al-MOFs are obtained by modifying a primary antioxidant with an Al-MOFs material.

[0014] In a specific embodiment, the modified Al-MOFs are prepared by the following method:

[0015] S1: Al(NO3)3·9H2O and organic ligand terephthalic acid are dissolved in water and placed in a hydrothermal reactor for reaction. After cooling, the precipitate is collected by centrifugation, washed and dried to obtain Al-based metal organic framework complex Al-MOFs white powder;

[0016] S2: Add N,N-dimethylformamide, Al-MOFs, primary antioxidant and esterification catalyst into the reaction container, cool after the reaction, remove solvent, wash and dry to obtain modified Al-MOFs.

[0017] In a specific embodiment, the molar ratio of Al(NO3)3·9H2O to terephthalic acid in step S1 is 1:1; preferably, the washing in step S1 is performed successively with deionized water, N,N-dimethylformamide and anhydrous ethanol.

[0018] In a specific embodiment, the mass ratio of Al-MOFs to the primary antioxidant in step S2 is 1:(2-4); preferably, the primary antioxidant is a hindered phenol antioxidant, preferably one or more selected from 1010 and 1076;

[0019] Preferably, the esterification catalyst in step S2 is p-toluenesulfonic acid, accounting for 2-3% of the total mass of the reactants;

[0020] Preferably, the reaction temperature in step S2 is 90-100° C. and the reaction time is 8-12 h;

[0021] Preferably, the washing in step S2 is performed with distilled water and then with anhydrous ethanol.

[0022] In a specific embodiment, the composite adsorbent is fly ash grafted carbon nanotubes;

[0023] Preferably, the fly ash grafted carbon nanotubes are prepared by the following steps:

[0024] 1) taking a certain amount of carbon nanotubes and placing them in concentrated acid at 40-80°C, ultrasonically washing for 2-4 hours, and repeatedly washing until the filtrate is neutral, and drying the product in an oven at 60-120°C to obtain acidified carbon nanotubes S-MWNT;

[0025] 2) Take an appropriate amount of fly ash, add sodium hydroxide for activation treatment, mix well, wash with deionized water until neutral, and then dry to constant weight to obtain alkalized fly ash;

[0026] 3) Take an appropriate amount of acidified carbon nanotubes in step 1) and an appropriate amount of alkalized fly ash in step 2) and add them into a three-necked flask, use tetrahydrofuran as solvent, and the reaction temperature is 50-80° C. The product is filtered and washed with tetrahydrofuran and acetone, and then dried to constant weight to obtain fly ash-grafted carbon nanotubes.

[0027] In a specific embodiment, the concentrated acid in step 1) is at least one of concentrated sulfuric acid, concentrated hydrochloric acid, and concentrated nitric acid, for example, the mass concentration of the concentrated acid is >98%, and preferably, the mass ratio of the carbon nanotubes to the concentrated acid is 1:(2-4);

[0028] Preferably, in step 2), the mass ratio of fly ash to sodium hydroxide is 1:(1.5-3.0);

[0029] Preferably, the mass ratio of the acidified carbon nanotubes to the alkalized fly ash in step 3) is 1:(1.5-2.0).

[0030] In a specific embodiment, the auxiliary antioxidant is a phosphite antioxidant or a thioester antioxidant, preferably at least one selected from 168, 626 or DSTP

[0031] Preferably, the lubricant is at least any one of zinc stearate, magnesium stearate, and ethylene bisstearamide;

[0032] Preferably, the filling material is at least one of talcum powder, calcium carbonate or barium sulfate; preferably talcum powder AH51205 or talcum powder AH51210.

[0033] On the other hand, the method for preparing the aforementioned flame retardant recycled polypropylene material comprises the following steps:

[0034] a) adding recycled polypropylene resin, modified Al-MOFs, composite adsorbent, auxiliary antioxidant and lubricant into a high-speed mixer according to proportion and mixing for 3-5 minutes;

[0035] b) adding the mixed materials in step a) into a parallel twin-screw extruder for melting, adding optional filler materials through side feeding, and then extruding and granulating to obtain a low-odor, aging-resistant flame-retardant recycled polypropylene material; preferably, the barrel temperature of the twin-screw extruder is 120-200° C., and the screw speed is 200-500 rpm.

[0036] Compared with the prior art, the present invention has the following technical advantages:

[0037] 1) Compared with the traditional primary antioxidant, the present invention adopts chemical modification to prepare the modified MOFs-primary antioxidant. The molecular weight of the primary antioxidant is further increased and adsorbed by the porous structure, so that the primary antioxidant is stably and evenly dispersed in the recycled material, avoiding its migration to the material surface and loss during the processing or later use, and continuously playing an anti-aging role during the use of the recycled material.

[0038] 2) The present invention also utilizes the porous structure of the Al-MOFs material to improve its adsorption capacity for volatile small molecules and reduce the odor of the recycled material, so that the recycled material has the ability of aging resistance and low odor, and can achieve an odor level of less than 3.5 and a performance retention rate of more than 75% after thermal oxidation aging at 150°C for 1000 hours.

[0039] 3) In the present invention, fly ash, an industrial solid waste, is added and modified by carbon nanotube grafting to form a composite adsorbent, thereby further expanding the specific surface area of ​​the fly ash and increasing the adsorption points, thereby effectively reducing the odor of the material.

[0040] 4) The fly ash added in the present invention is low-cost and widely available. Through grafting modification, the dispersion ability of carbon nanotubes in the composite material is greatly improved. In addition, as a nanofiller, it can effectively reduce the combustion rate of the composite material and improve the flame retardant properties of the composite material. DETAILED DESCRIPTION

[0041] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0042] A low-odor, aging-resistant, flame-retardant recycled polypropylene material comprising the following components:

[0043]

[0044] In the present invention, the recycled polypropylene resin is a recycled polypropylene material, and the filler content is preferably less than 5%; preferably, the melt index of the recycled polypropylene resin at 230°C and 2.16kg is 10-50g / 10min, for example including but not limited to 10g / 10min, 20g / 10min, 30g / 10min, 40g / 10min, and 50g / 10min.

[0045] In the present invention, the modified Al-MOFs are obtained by modifying the primary antioxidant through Al-MOFs material. The primary antioxidant is a hindered phenol primary antioxidant, such as any one of antioxidant 1010 and antioxidant 1076. Traditional antioxidants are prone to volatilization and migration during processing and use, causing large physical losses, which greatly reduces their antioxidant effect. At the same time, there are ester groups in the structure of hindered phenol primary antioxidants, which are hydrolyzed into small molecules in water and will migrate out of the material, and the antioxidant effect will decrease during daily use. After being modified by the MOFs of the present invention, the molecular weight of the primary antioxidant increases and is adsorbed by the porous structure, so it is not easy to migrate, can be better integrated into the material, and can continue to play a role after processing and use.

[0046] Among them, the method of modifying the main antioxidant by Al-MOFs material is:

[0047] S1: Al(NO3)3·9H2O and organic ligand terephthalic acid (H2BDC) are dissolved in water and placed in a hydrothermal reactor for reaction. After cooling, the precipitate is collected by centrifugation, washed and dried to obtain Al-based metal organic framework complex Al-MOFs white powder;

[0048] S2: DMF, Al-MOFs, primary antioxidant and esterification catalyst are added to the reaction container, and after the reaction, the mixture is cooled, the solvent is removed, washed and dried to obtain modified MOFs-primary antioxidant powder.

[0049] Wherein, the molar ratio of Al(NO3)3·9H2O to H2BDC in step S1 is 1:1; washing is performed successively with deionized water, N,N-dimethylformamide (DMF), and anhydrous ethanol.

[0050] The mass ratio of Al-MOFs to the primary antioxidant in step S2 is 1:(2-4), for example including but not limited to 1:2, 1:3, 1:4; the esterification catalyst is p-toluenesulfonic acid, accounting for 2-3% of the total mass of all reactants in step S2; the reaction temperature is 90-100°C, for example including but not limited to 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, and the reaction time is 8-12h, for example including but not limited to 9h, 10h, 11h; and the washing is carried out successively with distilled water and anhydrous ethanol.

[0051] The present invention utilizes Al-MOFs materials to modify the main antioxidant, thereby increasing the molecular weight of the main antioxidant and making the main antioxidant more stably and evenly dispersed in the recycled material, making it less likely to migrate to the surface of the material and cause loss during processing and later use. At the same time, the porous structure of MOFs is utilized to enable the recycled material to adsorb small molecular volatiles to reduce the odor of the material, thereby enabling the recycled material to have the capabilities of being resistant to aging and having low odor.

[0052] The present invention also adds fly ash grafted carbon nanotubes as a composite adsorbent to effectively reduce the odor of the composite material. In addition, by introducing carbon nanotubes, thanks to their special structural characteristics, they can effectively improve the aging resistance and flame retardant properties of the material. More importantly, fly ash has a wide source and low cost. This method can effectively solve its environmental pollution problem and has a good market application prospect.

[0053] In the present invention, the composite adsorbent is fly ash grafted carbon nanotubes, and the preparation method is as follows:

[0054] 1) taking a certain amount of carbon nanotubes and placing them in concentrated acid at 40-80°C, ultrasonically washing for 2-4 hours, and repeatedly washing until the filtrate is neutral, and drying the product in an oven at 60-120°C to obtain acidified carbon nanotubes S-MWNT;

[0055] 2) Take an appropriate amount of fly ash, add sodium hydroxide for activation treatment, mix well, wash with deionized water until neutral, and then dry to constant weight to obtain alkalized fly ash;

[0056] 3) Take an appropriate amount of acidified carbon nanotubes in step 1) and an appropriate amount of alkalized fly ash in step 2) and add them into a three-necked flask, use tetrahydrofuran as solvent, and the reaction temperature is 50-80° C. The product is filtered and washed with tetrahydrofuran and acetone, and then dried to constant weight to obtain fly ash-grafted carbon nanotubes.

[0057] Wherein, the concentrated acid in step 1) is at least one of sulfuric acid, hydrochloric acid and nitric acid, and the mass ratio of carbon nanotubes to concentrated acid is 1:(2-4), for example including but not limited to 1:2, 1:3, 1:4; the mass ratio between fly ash and sodium hydroxide in step 2) is 1:(1.5-3.0), for example including but not limited to 1:2, 1:2.5; the mass ratio of acidified carbon nanotubes to alkalized fly ash in step 3) is 1:(1.5-2.0), for example including but not limited to 1:1.6, 1:1.7, 1:1.8, 1:1.9.

[0058] The talc is used as a common filling material, for example, the talc is AH51205 and / or AH51210. The lubricant is one or more of zinc stearate and / or magnesium stearate and / or ethylene bis stearamide. The primary antioxidant is one or more of 1010 and / or 1076. The auxiliary antioxidant is one or more of 168, 626 or DSTP. These optional additives or fillers can be reasonably selected by those skilled in the art according to the needs of process processing. It will be understood by those skilled in the art that other processing aids may also be added.

[0059] The method for preparing the low-odor, aging-resistant, flame-retardant recycled polypropylene material comprises the following steps:

[0060] a) adding the recycled polypropylene resin, modified Al-MOFs, composite adsorbent, auxiliary antioxidant and lubricant into a high-speed mixer according to proportion and mixing for 3-5 minutes;

[0061] b) adding the mixed materials in step a) into a parallel twin-screw extruder for melting, adding talcum powder through side feeding, and then extruding and granulating to obtain a low-odor, aging-resistant recycled polypropylene material, wherein the barrel temperature of the extruder is 120-200° C. and the screw speed is 200-500 rpm.

[0062] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0063] In each embodiment and comparative example, the main raw materials come from the following sources:

[0064]

[0065] Unless otherwise specified, other raw materials and reagents were purchased from commercial sources.

[0066] In each embodiment and comparative example, the performance test parameters and corresponding test methods of the low odor aging-resistant material are as follows:

[0067] Test content unit Test Method Thermal Oxidative Aging / GB / T 7141 Flexural modulus MPa ISO 178 Tensile Strength MPa ISO 527 Izod unnotched impact strength <![CDATA[KJ / m 2 ]]> ISO 180 odor / PV3900 Horizontal burning rate mm / min UL94

[0068] The processing equipment used is:

[0069] Twin-screw extruder, Coperion, model ZSK 26Mc 18, aspect ratio 52, screw diameter 26 cm;

[0070] Injection molding machine, 100 ton Demag injection molding machine, model Systec 100 / 420-310C.

[0071] The equipment used is:

[0072] German ZWICK Z010TE universal testing machine;

[0073] German ZWICK HIT25P pendulum impact tester;

[0074] BINDER FD56 electric constant temperature blast drying oven;

[0075] Suzhou Jufu EAT-101 thermal oxygen aging chamber.

[0076] Wester RH6033A combustion test chamber

[0077] Example 1

[0078] 1.1 Preparation of modified Al-MOFs-primary antioxidant 1010:

[0079] S1: Preparation of Al-based metal organic framework complexes Al-MOFs materials

[0080] Add 37.5g of Al(NO3)3·9H2O to the reaction bottle, then add 16.6g of organic ligand terephthalic acid H2BDC, the molar ratio of the two is 1:1, add 300mL of deionized water and stir until dissolved. Then put it into a polytetrafluoroethylene hydrothermal reactor and keep it at 220℃ for 72h, cool it naturally to room temperature, collect the precipitate by high-speed centrifugation, wash it twice in the order of deionized water, N,N-dimethylformamide (DMF), and ethanol, and finally dry it in a forced air drying oven at 70℃ for 12h to obtain the pure white powdery final product Al-MOFs.

[0081] S2: Preparation of modified Al-MOFs (1)

[0082] Add 10 mL of DMF to the reaction bottle, then add 4 g of Al-MOFs and 8 g of antioxidant 1010, and then add 0.24 g of esterification catalyst p-toluenesulfonic acid. After stirring evenly, place the reaction bottle in a 90°C water bath and react for 8 hours. Cool the solution to room temperature, remove the solvent through a high-speed centrifuge, wash twice with distilled water and anhydrous ethanol respectively, and finally dry it in a forced air drying oven at 80°C for 12 hours to obtain modified Al-MOFs (1).

[0083] 1.2 Preparation of composite adsorbent - fly ash grafted carbon nanotubes:

[0084] 1) 30 g of carbon nanotubes were placed in 60 g of concentrated sulfuric acid at 40° C. and ultrasonicated for 2 hours. The product was washed repeatedly until the filtrate was neutral and then dried in an oven at 60° C. to obtain acidified carbon nanotubes S-MWNT.

[0085] 2) Take 50g of fly ash, add 75g of sodium hydroxide to activate it, mix well, wash it with deionized water until it is neutral, and then dry it to constant weight to obtain alkalized fly ash.

[0086] 3) 30 g of the acidified carbon nanotubes in step 1) and 45 g of the alkalized fly ash in step 2) were mixed and added into a three-necked flask, tetrahydrofuran was used as solvent, the reaction temperature was 50° C., the product was filtered and washed with tetrahydrofuran and acetone, and then dried to constant weight to obtain fly ash grafted carbon nanotubes.

[0087] 1.3 Preparation of low odor and aging-resistant flame-retardant recycled polypropylene materials

[0088] a) Regenerated PP1, composite adsorbent, modified Al-MOFs (1), antioxidant 168, antioxidant DSTP and calcium stearate were added into a high-speed mixer at the ratio of 98.9 parts, 0.4 parts, 0.2 parts, 0.1 parts, 0.2 parts and 0.2 parts, and mixed for 3 minutes.

[0089] b) adding the mixed materials in step a) into the main feed of a twin-screw extruder. The extrusion conditions are as follows: screw speed is 200 rpm, and the screw temperature is set in stages from the feed port to the die head as follows: 120°C, 175°C, 180°C, 175°C, 180°C, 185°C, 175°C, 175°C, 175°C, 175°C, 175°C, 175°C.

[0090] Example 2

[0091] 2.1 Preparation of modified MOFs-antioxidant 1010:

[0092] S1: Prepare Al-based metal organic framework complex Al-MOFs material according to the method in Example 1.

[0093] S2: Preparation of modified Al-MOFs (2)

[0094] Add 20 mL of DMF to the reaction bottle, then add 4 g of Al-MOFs and 16 g of antioxidant 1010, and then add 0.6 g of esterification catalyst p-toluenesulfonic acid. After stirring evenly, place the reaction bottle in a 100°C water bath and react for 12 hours. Cool the solution to room temperature, remove the solvent through a high-speed centrifuge, wash twice with distilled water and anhydrous ethanol respectively, and finally dry it in a forced air drying oven at 80°C for 12 hours to obtain modified Al-MOFs (2).

[0095] 2.2 Preparation of composite adsorbent - fly ash grafted carbon nanotubes:

[0096] 1) 45 g of carbon nanotubes were placed in 180 g of concentrated sulfuric acid, and ultrasonically treated at 80° C. for 4 hours. The product was washed repeatedly until the filtrate was neutral, and then dried in an oven at 120° C. to obtain acidified carbon nanotubes S-MWNT.

[0097] 2) Take 30g of fly ash, add 90g of sodium hydroxide to activate it, mix well, wash it with deionized water until it is neutral, and then dry it to constant weight to obtain alkalized fly ash.

[0098] 3) 30 g of the acidified carbon nanotubes in step 1) and 60 g of the alkalized fly ash in step 2) were mixed and added into a three-necked flask, tetrahydrofuran was used as solvent, the reaction temperature was 80° C., the product was filtered and washed with tetrahydrofuran and acetone, and then dried to constant weight to obtain fly ash grafted carbon nanotubes.

[0099] 2.3 Preparation of low-odor, aging-resistant, flame-retardant recycled polypropylene materials

[0100] a) Regenerated PP2, composite adsorbent, modified Al-MOFs (2), antioxidant 168, antioxidant DSTP and calcium stearate were added into a high-speed mixer in the proportions of 56.1 parts, 1.2 parts, 0.8 parts, 0.5 parts, 0.8 parts and 0.6 parts, and mixed for 5 minutes.

[0101] b) The mixed materials in step a) are added to the main feed of the twin-screw extruder, and 40 parts of talcum powder AH51210 are added to the side feed. The extrusion conditions are: screw speed 500 rpm, and the screw temperature from the feed port to the die is set in sections as follows: 140°C, 185°C, 190°C, 185°C, 190°C, 200°C, 195°C, 185°C, 185°C, 185°C, 185°C.

[0102] Example 3

[0103] 3.1 Preparation of modified Al-MOFs (3):

[0104] S1: Prepare Al-based metal organic framework complex Al-MOFs material according to the method in Example 1.

[0105] S2: Preparation of modified Al-MOFs (3)

[0106] Add 20 mL of DMF to the reaction bottle, then add 5 g of Al-MOFs and 15 g of antioxidant 1010, and then add 0.5 g of esterification catalyst p-toluenesulfonic acid. After stirring evenly, place the reaction bottle in a 95°C water bath and react for 10 hours. Cool the solution to room temperature, remove the solvent through a high-speed centrifuge, wash twice with distilled water and anhydrous ethanol respectively, and finally dry it in a forced air drying oven at 80°C for 12 hours to obtain modified Al-MOFs (3).

[0107] 3.2 Preparation of composite adsorbent - fly ash grafted carbon nanotubes:

[0108] 1) 45 g of carbon nanotubes were placed in 135 g of concentrated sulfuric acid, and ultrasonicated at 60° C. for 3 hours. After repeated washing until the filtrate was neutral, the product was dried in an oven at 100° C. to obtain acidified carbon nanotubes S-MWNT.

[0109] 2) Take 30g of fly ash, add 60g of sodium hydroxide to activate it, mix well, wash with deionized water to neutrality, and then dry to constant weight to obtain alkalized fly ash.

[0110] 3) 30 g of the acidified carbon nanotubes in step 1) and 50 g of the alkalized fly ash in step 2) are mixed and added into a three-necked flask, tetrahydrofuran is used as solvent, the reaction temperature is 70° C., the product is filtered and washed with tetrahydrofuran and acetone, and then dried to constant weight to obtain fly ash grafted carbon nanotubes.

[0111] 3.3 Preparation of low-odor, aging-resistant, flame-retardant recycled polypropylene materials

[0112] a) adding 40 parts, 37.5 parts, 0.8 parts, 0.5 parts, 0.2 parts, 0.6 parts and 0.4 parts of regenerated PP1 and PP2, composite adsorbent, modified Al-MOFs (3), antioxidant 168, antioxidant DSTP and calcium stearate into a high-speed mixer and mixing for 4 minutes;

[0113] b) The mixed materials in step a) are added to the main feed of the twin-screw extruder, and 20 parts of talcum powder AH51205 are added to the side feed. The extrusion conditions are: screw speed is 400 rpm, and the screw temperature is set in stages from the feed port to the die: 140°C, 185°C, 190°C, 185°C, 190°C, 200°C, 195°C, 185°C, 185°C, 185°C, 185°C.

[0114] Comparative Example 1

[0115] Using commercially available antioxidant 1010 and fly ash as raw materials, without chemical grafting and modification, recycled polypropylene material was prepared according to the method a) and b) in Example 2, except that the raw material proportions in Table 1 were different, and modified Al-MOFs material and fly ash grafted carbon nanotubes were not used.

[0116] Comparative Example 2

[0117] Using commercially available antioxidant 1010 as raw material, without chemical grafting and modification, recycled polypropylene material was prepared according to the method a) and b) in Example 2, except that the raw material ratios in Table 1 were different and modified Al-MOFs material was not used.

[0118] Comparative Example 3

[0119] Commercially available fly ash was used as raw material, without chemical grafting and modification, and recycled polypropylene material was prepared according to the method a) and b) in Example 2, except that the raw material ratios in Table 1 were different and fly ash was not used to graft carbon nanotubes.

[0120] The composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were processed into strips in an injection molding machine, and the temperatures of the screw sections were set to 190° C., 205° C., 210° C., and 205° C., respectively. The test results of various properties of the injection molded strips are shown in Table 2.

[0121] Table 1 Raw materials and dosage (g) in Examples 1-3 and Comparative Examples 1-3

[0122]

[0123]

[0124] Table 2 Performance test results of Examples 1-3 and Comparative Examples 1-3

[0125]

[0126] It can be seen from Comparative Examples 1 to 3 and Examples 1 to 3 that the modified Al-MOFs and fly ash grafted modified carbon nanotubes added in the examples can significantly improve the aging resistance of the material, reduce the odor level of the material, and at the same time have excellent flame retardant properties.

[0127] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A low-odor, aging-resistant, flame-retardant recycled polypropylene material, characterized in that: Contains the following ingredients: Recycled polypropylene resin 56.1-98.9 parts; Composite adsorbent 0.4-1.2 parts; Modified Al-MOFs 0.2-0.8 parts; Auxiliary antioxidant 0.3-1.3 parts; Lubricant 0.2-0.6 parts; Filling material 0-40 parts; The composite adsorbent is fly ash grafted carbon nanotubes; The modified Al-MOFs are obtained by modifying the main antioxidant with Al-MOFs materials; the modified Al-MOFs are prepared by the following method: S1: Al(NO3)3·9H2O and organic ligand terephthalic acid are dissolved in water and placed in a hydrothermal reactor for reaction. After cooling, the precipitate is collected by centrifugation, washed and dried to obtain Al-based metal organic framework complex Al-MOFs white powder; S2: Add N,N-dimethylformamide, Al-MOFs, primary antioxidant and esterification catalyst into the reaction container, cool after the reaction, remove the solvent, wash and dry to obtain modified Al-MOFs.

2. The flame retardant recycled polypropylene material according to claim 1, characterized in that: Contains the following ingredients: Recycled polypropylene resin 67.2-78.3 parts; Composite adsorbent 0.5-1.0 part; Modified Al-MOFs 0.4-0.6 parts; Auxiliary antioxidant 0.5-0.8 parts; Lubricant 0.3-0.4 parts; 20-30 parts of filling material.

3. The flame retardant recycled polypropylene material according to claim 1 or 2, characterized in that: The regenerated polypropylene resin is recycled polypropylene regenerated material.

4. The flame retardant recycled polypropylene material according to claim 3, characterized in that: The recycled polypropylene resin is a recycled polypropylene material with a filler content of less than 5%.

5. The flame retardant recycled polypropylene material according to claim 3, characterized in that: The regenerated polypropylene resin has a melt index of 10-50 g / 10 min at 230° C. and 2.16 kg.

6. The flame retardant recycled polypropylene material according to claim 1, characterized in that: In step S1, the molar ratio of Al(NO3)3·9H2O to terephthalic acid is 1:

1.

7. The flame retardant recycled polypropylene material according to claim 6, characterized in that: In step S1, the washing is performed successively with deionized water, N,N-dimethylformamide, and anhydrous ethanol.

8. The flame retardant recycled polypropylene material according to claim 1, characterized in that: In the step S2, the mass ratio of Al-MOFs to the primary antioxidant is 1:(2-4).

9. The flame retardant recycled polypropylene material according to claim 8, characterized in that: The main antioxidant is a hindered phenol antioxidant.

10. The flame retardant recycled polypropylene material according to claim 9, characterized in that: The primary antioxidant is selected from one or both of 1010 and 1076.

11. The flame retardant recycled polypropylene material according to claim 8, characterized in that: In step S2, the esterification catalyst is p-toluenesulfonic acid, which accounts for 2-3% of the total mass of the reactants.

12. The flame retardant recycled polypropylene material according to claim 8, characterized in that: In step S2, the reaction temperature is 90-100° C. and the reaction time is 8-12 h.

13. The flame retardant recycled polypropylene material according to claim 8, characterized in that: The washing in step S2 is performed by washing with distilled water and anhydrous ethanol in sequence.

14. The flame retardant recycled polypropylene material according to claim 1 or 2, characterized in that: The fly ash grafted carbon nanotubes are prepared by the following steps: 1) Take a certain amount of carbon nanotubes and place them in concentrated acid at 40-80°C, ultrasonicate for 2-4 hours, wash repeatedly until the filtrate is neutral, and dry the product in an oven at 60-120°C to obtain acidified carbon nanotubes S-MWNT; 2) Take an appropriate amount of fly ash, add sodium hydroxide for activation treatment, mix well, wash with deionized water until neutral, and then dry to constant weight to obtain alkaline fly ash; 3) Take an appropriate amount of acidified carbon nanotubes in step 1) and an appropriate amount of alkalized fly ash in step 2) and add them into a three-necked flask, use tetrahydrofuran as solvent, and the reaction temperature is 50-80°C. The product is filtered and washed with tetrahydrofuran and acetone, and then dried to constant weight to obtain fly ash-grafted carbon nanotubes.

15. The flame retardant recycled polypropylene material according to claim 14, characterized in that: The concentrated acid in step 1) is at least one of concentrated sulfuric acid, concentrated hydrochloric acid and concentrated nitric acid.

16. The flame retardant recycled polypropylene material according to claim 15, characterized in that: The mass ratio of carbon nanotubes to concentrated acid is 1:(2~4).

17. The flame retardant recycled polypropylene material according to claim 14, characterized in that: In the step 2), the mass ratio of fly ash to sodium hydroxide is 1:(1.5-3.0).

18. The flame retardant recycled polypropylene material according to claim 14, characterized in that: The mass ratio of the acidified carbon nanotubes to the alkalized fly ash in step 3) is 1:(1.5-2.0).

19. The flame retardant recycled polypropylene material according to claim 1 or 2, characterized in that: The auxiliary antioxidant is a phosphite antioxidant or a thioester antioxidant.

20. The flame retardant recycled polypropylene material according to claim 19, characterized in that: The auxiliary antioxidant is selected from at least any one of 168, 626 or DSTP.

21. The flame retardant recycled polypropylene material according to claim 1 or 2, characterized in that: The lubricant is at least any one of zinc stearate, magnesium stearate, and ethylene bis stearamide.

22. The flame retardant recycled polypropylene material according to claim 1 or 2, characterized in that: The filling material is at least one of talc, calcium carbonate or barium sulfate.

23. The flame retardant recycled polypropylene material according to claim 22, characterized in that: The filling material is talcum powder AH51205 or talcum powder AH51210.

24. The method for preparing the flame retardant recycled polypropylene material according to any one of claims 1 to 23, characterized in that: The following steps are involved: a) Add the recycled polypropylene resin, modified Al-MOFs, composite adsorbent, auxiliary antioxidant and lubricant into a high-speed mixer according to the proportion and mix for 3-5 minutes; b) The mixed materials in step a) are added into a parallel twin-screw extruder for melting, and optional filler materials are added through side feeding, followed by extrusion and granulation to obtain a low-odor, aging-resistant, flame-retardant recycled polypropylene material.

25. The preparation method according to claim 24, characterized in that: The barrel temperature of the twin-screw extruder is 120-200°C, and the screw speed is 200-500 rpm.

Citation Information

Patent Citations

  • Aging-resistant HIPS expanded plastic and preparation method thereof

    CN108530786A

  • Multifunctional master batch for regenerated plastic

    CN109503919A

  • Low-cost polyvinyl chloride plastic pipe and preparation method thereof

    CN105860342A

  • Low-odor heat-aging-resistant glass fiber reinforced polypropylene material and preparation method thereof

    CN110922678A

  • Super-hydrophobic low-precipitation degradable material and preparation method thereof

    CN114085539A